The Role of Financial Attitudes in the Influence of Financial Literacy on the Financial Behavior of Generation Z - Dwi Putri, Tyara; Azliyanti, Elfitra; Dharma, Surya; Irda, Irda (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze the effect of financial literacy on students' financial behavior, with personal financial attitudes as a mediating variable. This quantitative study used a questionnaire as a data collection technique with 130 Universitas Bung Hatta students as respondents. The sampling technique used was probability sampling, which provided equal opportunities for Universitas Bung Hatta students to be selected as research samples. The results were processed using the SMART-PLS application using the Measurement Model Assessment (MMA), R-Square, and Structural Model Assessment (SMA) procedures. The results of this study indicate that 1) financial literacy has a positive effect on students' financial behavior, 2) financial literacy has a positive effect on personal financial attitudes, 3) personal financial attitudes have a positive effect on students' financial behavior, and 4) personal financial attitudes mediate the effect of financial literacy on students' financial behavior.